Use of pressure distribution analysis to estimate fluid forces around a foot during breaststroke kicking - Tsunokawa, T.; Nakashima, M.; Takagi, H. (Sports Engineering, 2015)
The aims of this study were twofold: first, use a robotic leg to investigate the reliability of estimating fluid forces acting on the foot during breaststroke kicking and second, test the utility for actual human swimmer`s kicking. In this study, fluid forces were estimated from the measurement of pressure distribution around a foot. In the first experiment, the reliability of the estimated measurements was evaluated in a series of experiments using a robotic leg that can reproduce breaststroke-kicking motions. The resulting estimates correlated significantly with the fluid force acting on the foot model that was measured by a load cell (r = 0.62-0.92). In the second experiment, breaststroke-kicking motions of human swimmers were analyzed using the methodology tested in the first experiment. The estimated fluid forces showed significant correlation with the velocities of the human swimmers (r = 0.87). Furthermore, this methodology can monitor intra-cycle force fluctuations. We conclude that the present methodology can be used to evaluate breaststroke-kicking motions quantitatively, thereby assisting swimmers and their coaches in better understanding of breaststroke kicking.